Section 1Tunable broadband terahertz absorbers based on multiple layers of graphene ribbons. Issue 1 (December 2017) - Chen, Dingbo; Yang, Junbo; Zhang, Jingjing; Huang, Jie; Zhang, Zhaojian
Abstract A novel metamaterial structure consisting of multiple graphene/dielectric layers and metallic substrate is proposed to achieve the broadband absorption response at terahertz (THz) frequencies. Utilizing the phase modulation effect generated by graphene ribbons, the bright-dark field is formed to suppress the reflection based on interference theory in a wide period. By irregularly stacking four graphene ribbons of varying widths on four dielectric layers with unequal thickness in a period, we merge successive absorption peaks into a broadband absorption spectrum successfully. The absorption decreases with fluctuations as the incident angle increases. The position of the absorption spectrum can be dynamically tuned by a small change in the Fermi level of graphene instead of re-optimizing and re-fabricating the device. In addition, the bandwidth of the absorber can be further improved by means of increasing the graphene/dielectric layers. The structure proposed in this paper has potential applications in tunable terahertz photonic devices such as dynamic broadband filters, modulators and sensors.